Viburnum Leaf Beetle Pyrrhalta viburni (Paykull) (Insecta: Coleoptera: Chrysomelidae) - Jamba Gyeltshen; Amanda Hodges (EDIS)
This EDIS publication is an alternate version of a page published first on the Featured Creatures website. The Featured Creatures collection provides in-depth profiles of insects, nematodes, arachnids and other organisms relevant to Florida. These profiles are intended for the use of interested laypersons with some knowledge of biology as well as academic audiences. This 5-page fact sheet that discusses the viburnum leaf beetle (VLB) was written by Jamba Gyeltshen and Amanda Hodges, and published by the UF Entomology and Nematology Department, February 2016.